Report on the third regional community of practice on mine regulation and occupational health and safety, 21-22 September 2019 - Khoza, Norman; Chamdimba, Chimwemwe; Mohamed, Mohamed A.; Moyo, Dingani (Mettamedia (Pty) Ltd, 2022)
Through the Southern African Tuberculosis and Health Systems Support (SATBHSS) Project, countries have committed to rolling out a standardised package of occupational health services and mining safety standards as part of the response to tuberculosis (TB) and occupational lung diseases (OLDs). This commitment is implemented through (i) capacity strengthening of public sector agencies responsible for mine safety inspections; (ii) expansion of periodic medical screening and referral of diagnosed cases of OLDs and other diseases, in line with regional and international standards; and (iii) development and strengthening of care programmes for OLDs. The community of practice (CoP) on mine health regulation and occupational health and safety (OHS) has been constituted to roll out a standardised package of occupational health services and mining safety standards.